SYMBOLIC MODELING IN PSYCHOEDUCATIONAL GROUPS: ADVANCING LEARNING STRATEGIES AMONG EARLY ADOLESCENTS - Abil Anggara Pratama; Nasruliyah Hikmatul Maghfiroh; Bhenita Sukmawati (EDUCATIONE, 2025)
Many junior high school students struggle with low self-regulated learning and ineffective learning strategies, resulting in poor academic achievement and dependence on teacher direction. This study aims to analyze the effectiveness of psychoeducational group using symbolic modeling techniques in improving learning strategies among seventh-grade students at SMP Al-Hidayah Wuluhan. Employing a true experimental pre-test post-test control group design, eight purposively selected students were divided into experimental and control groups. The intervention consisted of six psychoeducational group sessions using symbolic modeling via videos and pictorial media, while the control group received no additional treatment. Data were collected using a 30-item learning strategies questionnaire and counselor observations, then analyzed with descriptive statistics and inferential tests (paired sample t-test, independent samples t-test, and Wilcoxon test). The results showed a statistically significant increase in learning strategy scores in the experimental group (mean improvement: 2.30 to 3.95, p < 0.01, large effect size), particularly in study scheduling, resource selection, and metacognitive monitoring. The control group showed no significant change. The findings confirm that symbolic modeling, when embedded in psychoeducational group, accelerates the acquisition of adaptive learning behaviors and promotes student self-regulation. This research extends Bandura’s social cognitive theory by demonstrating the effectiveness of symbolic modeling for cognitive strategy development. The study offers practical implications for integrating digital media in school counseling and recommends further research with larger and more diverse samples to explore long-term effects and optimize implementation.